Lexical and Grammatical Problems Coped with Communication Strategies - Triassanti, Risa; Mansur, Mansur; Wardhono, Agus (Universitas Muhammadiyah Gresik, 2018)
Based on preliminary observation most students feel hesitate to continue English conversation when they lacked of vocabularies and structured grammatical sentences. The students prefer to stop speaking. Therefore they need strategies to keep the communication on. Dealing with the problems, the present study investigates the lexical and grammatical communication problems that can be managed by communication strategies. An observation was done to 60 students in different levels of proficiency. it was revealed that there was a significant difference in the frequency and percentage of learners’ solved lexical problems (72.2 %) and grammatical problems (27.8%). The results drawn from these items were that EFL students used communication strategies on lexical problems are more frequent than used communication strategies on grammatical problems. This strategy is one small step towards clarifying the balanced of using communication strategy on lexical and grammatical problems in communication.